Effects of a 4-week interval training program using vVO2max and Tmax on performance in middle distance athletes - Smith, T. P.; McNaughton, L. R.; Coombes, J. S. (Medicine & Science in Sports & Exercise, 1999)
Velocity at VO2max (vVO2max) and maximum time at that velocity (Tmax) are used to deign individual training programs. Previous work showed that significant performance improvements resulted from interval training a vVO2max and 60% Tmax. This study evaluated the effects of training for four weeks with an exercise intensity between 60-75% of Tmax as the interval duration. Trained male middle-distance runners (N = 8) were measured for physiological factors, a 3000m running time-trial, and three treadmill tests to determine Tmax. Training was on a motorized treadmill. Ss were re-tested following training. Significant increases in average vVO2max, Tmax, and VO2max were recorded after training. The 3000m time-trial performances were significantly improved. Implication. As the pace of training approaches race velocities, running velocity and physiological adaptations improve.